PENGENALAN TEKNOLOGI INFORMASI PADA UMKM TEH KELOR AGAR MAMPU BERSAING DI MASA PANDEMI COVID-19 - Sri Karnila; Neni Purwati; Hendra Kurniawan; Nurjoko Nurjoko (Jurnal Abdimas Bina Bangsa, 2021)
The COVID-19 pandemic has had a very significant impact on all lines of human life. Usaha Mikro Kecil dan Menengah (UMKM) which were originally able to conduct sales conventionally through stalls or shops, which with limitations must transform to selling online. The method used is the activity socialization stage, preparation stage, implementation stage and reporting stage. Pengabdian Kepada Masyarakat (PKM) activity in Pidada Village, Panjang District, Bandar Lampung Regency, we carried out activities on developing UMKMs based on local wisdom, by providing an introduction to the use of information technology. Kelor tea is one of the SMEs in Pidada village which in its production process empowers local women to increase the economic income of Pidada villagers. During PKM at UMKM Teh Kelor we made several innovations, packaging by labeling and branding products, as well as marketing products online. The use of information technology for the sale of Moringa tea is carried out so that MSMEs of Moringa Tea are able to compete during this COVID-19 Pandemic